2014
DOI: 10.3109/16066359.2013.877453
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of heroin and methamphetamine use among homeless male ex-jail and prison offenders

Abstract: Homeless men exiting California State jails and prisons are a heterogeneous community with varied childhood, incarceration and drug use histories. This cross-sectional study assessed whether homeless men who were discharged from either jail or prison into a residential substance abuse treatment program, differed in terms of methamphetamine and heroin use. This study utilized baseline data collected on 540 recently paroled men randomized to one of three programs that assessed the impact of a peer coaching inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…In contrast to common perceptions about the use of MA leading to violent behaviour, the findings of our review identified only three studies demonstrating a correlation between MA use and the perpetration of violence among persons experiencing homelessness (Fast et al, 2014;Martin et al, 2006;Nyamathi et al, 2014a). The existence of only three studies with these findings suggests that either existing literature has failed to demonstrate an empirical relationship between MA use and the perpetration of violence, or that this area of research is underdeveloped.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…In contrast to common perceptions about the use of MA leading to violent behaviour, the findings of our review identified only three studies demonstrating a correlation between MA use and the perpetration of violence among persons experiencing homelessness (Fast et al, 2014;Martin et al, 2006;Nyamathi et al, 2014a). The existence of only three studies with these findings suggests that either existing literature has failed to demonstrate an empirical relationship between MA use and the perpetration of violence, or that this area of research is underdeveloped.…”
Section: Discussioncontrasting
confidence: 80%
“…Four (20%) of the included studies explored the relationship between MA use, crime and physical altercations (Fast et al., 2014; Martin et al., 2006, 2009; Nyamathi et al., 2014a). In two of these studies, MA use was linked to the perpetration of a violent crime (Fast et al., 2014; Nyamathi et al., 2014a). This was described by a participant in one of these studies as: ‘…you looooooooove getting into trouble when you're on meth though.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding also suggests African American men involved in the criminal justice system may encounter unique sociodemographic and psychosocial risk factors, which are not being captured in extant literature, conceptualizing NMOU as a ‘White problem’ in suburban (Cicero et al, 2014) and rural areas (Love et al, 2016). Consistent with the availability-proneness theory (Smart, 1980), these psychosocial risk factors may include: re-entry stress (Baron et al, 2013; Lee et al, 2017), mental illness (Broz & Oullet, 2010), homelessness (Nyamathi et al, 2014), and poverty (Bright, 2012). In the absence of adequate resources, these psychosocial stressors may persist and increase their proneness to engage in substance use, criminal behavior (Mahaffey et al, 2017), and consequently, involved in the criminal justice system; resulting in a potentially cyclical pattern of substance use (Baillargeon et al, 2009).…”
Section: 0 Discussionmentioning
confidence: 98%